Developing a learning management system for critical literacy course: A need analysis - Tara Mustikaning Palupi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
In preparing the students to have the ability to interpret texts using critical lenses, to challenge the power relations within the messages and communicate actively in multimodal context, there is a need and urgency of the hybrid learning process to take place. As part of multi-years’ research and development which aims to develop digital module and learning management systems (LMS) for the students, this preliminary needs-based research focuses on the students’ and lecturers’ perceptions regarding the need for developing LMS in the Critical Literacy course in Bachelor of English Language Education, Universitas Negeri Jakarta. The research participants were thirty-two students, and a lecturer who responded to questionnaires, interviews to lecturer, and focus group discussions. The research data was the students’ needs based on Hutchinson and Water’s theory which could be divided into target needs (necessities, lacks and wants) and learning needs.  The study was conducted with the qualitative approach with the Successive Approximation Model (SAM) which focuses on Preparation Phase research design. Throughout the information gathering and the Savvy Start, the phase rotated through needs analysis and library study. The results demonstrate that there is a gap between the expected outcomes of the Critical Literacy course and students' ability to understand various texts, especially in understanding the interpretation of data in the form of graphs, tables, and numbers. Also, students need exposure to various texts such as news items, critical analysis of texts, and current issues in education. While the difficulty experienced by lecturers when teaching is that students' language skills (especially reading) are very varied. Also, the lecturer and students want Critical Literacy material that makes students think critically about topics related to critical literacy theory, strategy, and its practice. The preferred activities in this course include debates, discussions, criticizing social campaigns, advertisements and short films, and topics on digital literacy. By this, developing a ready-to-use digital English learning materials that correspond to the students’ and lecturer’s is exigent.Ketwords: needs analysis; critical literacy course; The successive approximation model (SAM)Mengembangkan learning management system pada mata kuliah critical literacy: Sebuah analisa kebutuhanDalam rangka mempersiapkan mahasiswa untuk memiliki kemampuan menginterpretasikan teks dengan menggunakan kemampuan berpikir kritis, menantang relasi kuasa dalam pesan dan berkomunikasi secara aktif dalam konteks multimodal, terdapat kebutuhan dan urgensi agar proses pembelajaran hybrid dapat berlangsung. Sebagai bagian dari penelitian dan pengembangan berkelanjutan yang bertujuan untuk mengembangkan modul digital dan learning management system (LMS) bagi mahasiswa, penelitian tahun pertama berbasis kebutuhan ini berfokus pada perspective mahasiswa dan dosen berkaitan dengan kebutuhan pengembangan LMS pada mata kuliah Critical Literacy di Prodi Pendidikan Bahasa Inggris, Universitas Negeri Jakarta. Tiga puluh dua orang mahasiswa, dan seorang dosen mengisi angket, melakukan focus group discussion dan wawancara dengan dosen. Data penelitian adalah kebutuhan siswa berdasarkan teori Hutchinson and Water yang dapat dibagi menjadi kebutuhan target (necessities, lacks and wants) dan kebutuhan belajar. Penelitian dilakukan dengan pendekatan kualitatif menggunakan Successive Approximation Model (SAM) yang menitikberatkan pada desain Preparation Phase. Dalam tahap ini dilakukan pengumpulan informasi dan studi pustaka. Hasil penelitian menunjukkan bahwa terdapat kesenjangan antara hasil yang diharapkan dari mata kuliah Critical Literacy dengan kemampuan siswa dalam memahami berbagai teks, terutama dalam memahami interpretasi data dalam bentuk grafik, tabel, dan angka. Selain itu, siswa membutuhkan banyak paparan berbagai teks seperti news item, analisis kritis teks, dan isu-isu terkini dalam pendidikan. Sedangkan kesulitan yang dialami dosen saat mengajar adalah kemampuan berbahasa mahasiswa (khususnya membaca) yang sangat bervariasi. Selain itu, dosen dan mahasiswa menginginkan materi Critical Literacy yang mampu membuat mahasiswa berpikir kritis dengan topik-topik yang berkaitan dengan teori, strategi, dan praktik literasi kritis. Kegiatan yang disukai dalam mata kuliah ini antara lain debat, diskusi, kritik kampanye sosial, iklan dan film pendek, serta topik mengenai literasi digital. Oleh karena itu, pengembangan materi pembelajaran bahasa Inggris digital yang siap pakai yang sesuai dengan kebutuhan mahasiswa dan dosen menjadi sangat mendesak untuk dibuat.Kata kunci: analisis kebutuhan; mata kuliah critical literacy; The successive approximation model (SAM)